Factors that Affect Purchase Decisions on Marketplace Users with Brand Image as A Mediating Variable - Achmad, Nur; Fatah, M. Miftahul; Wahyuningrum, Dinda Daniar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study aims to investigate the impact of brand ambassadorship (X1), pricing strategies (X2), and promotional activities (X3) on purchasing decisions (Y) among marketplace users, with a particular focus on the mediating influence of brand image (Z). Methodology: A sample of 390 marketplace users, selected through convenience sampling, underwent analysis employing Structural Equation Modeling (SEM) Partial Least Squares (PLS). Results: Brand ambassadors, pricing strategies, and promotional activities collectively positively and significantly influence brand image. Pricing strategies notably affect purchasing decisions. While brand ambassadors and promotional activities positively influence purchasing decisions, their effects are not statistically significant. Moreover, brand image significantly impacts purchasing decisions and serves as a mediator for all independent variables. Applications/Originality/Value: This study contributes to a deeper comprehension of consumer behaviour within marketplaces, furnishing practical insights for marketers. The identified mediating role of brand image enriches existing literature, underscoring its pivotal role in shaping consumer choices and decision-making processes.